The last bastion? X chromosome genotyping of Anopheles gambiae species pair males from a hybrid zone reveals complex recombination within the major candidate 'genomic island of speciation'. Issue 22 (3rd November 2016) - Caputo, Beniamino; Pichler, Verena; Mancini, Emiliano; Pombi, Marco; Vicente, José L.; Dinis, Joao; Steen, Keith; Petrarca, Vincenzo; Rodrigues, Amabelia; Pinto, Joao; della Torre, Alessandra; Weetman, David
Abstract: Speciation with gene flow may be aided by reduced recombination helping to build linkage between genes involved in the early stages of reproductive isolation. Reduced recombination on chromosome X has been implicated in speciation within the Anopheles gambiae complex, species of which represent the major Afrotropical malaria vectors. The most recently diverged, morphologically indistinguishable, species pair, A. gambiae and Anopheles coluzzii, ubiquitously displays a 'genomic island of divergence' spanning over 4 Mb from chromosome X centromere, which represents a particularly promising candidate region for reproductive isolation genes, in addition to containing the diagnostic markers used to distinguish the species. Very low recombination makes the island intractable for experimental recombination studies, but an extreme hybrid zone in Guinea Bissau offers the opportunity for natural investigation of X‐island recombination. SNP analysis of chromosome X hemizygous males revealed: (i) strong divergence in the X‐island despite a lack of autosomal divergence; (ii) individuals with multiple‐recombinant genotypes, including likely double crossovers and localized gene conversion; (iii) recombination‐driven discontinuity both within and between the molecular species markers, suggesting that the utility of the diagnostics is undermined under high hybridization. The largely, but incompletely protected nature of the X centromeric genomic island is consistent with a primary candidate area for accumulation of adaptive variants driving speciation with gene flow, while permitting some selective shuffling and removal of genetic variation.